Entre as memórias do campo das vertentes: uma história da formação de professores de Matemática da Fundação de Ensino Superior de São João del-Rei (FUNREI) no período de 1987 a 2001 - Paulo Henrique Apipe Avelar de Paiva (2016)
course of Sciences in Foundation of Higher Education of São João del Rei, from 1987 to 2001. For this, we focus on the structure of the course, internal and external, on the movement of the newly created institution and the role attributed to mathematics before and after the creation ofqualifications in Physics and Chemistry. In our methodological route, we checked particularly relevant to oral history and interviews conducted with nine people involved with the course focused during the reporting period. The nine narratives drawn from recorded interviews, along with written documents concerning the research object, composed our material of analysis of convergences, differences and peculiarities that have shaped our story about the formation of mathematics teachers in the course of Sciences of the Higher Education Foundation of São João del Rei. The results show, above all, the importance of Science course in the area to which the institution belonged to little emphasis on Mathematics on a course that allowed the finisher course to teach this course, the importance of creating two qualifications in the course and hisrole in creating Full Degree in Mathematics from UFSJ. Our research aims, also, to contribute to a larger scope project, which intends to map the preparation and performance of mathematics teachers in Brazil, and is being developed by the Group "Oral History and Mathematics Education" - GHOEM, of which we are part.